PENGARUH PERHATIAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA SMP - Syaharuddin Syaharuddin (STKIP Andi Matappa, 2021)
This type of research uses an ex-post facto approach to examine learning outcomes influenced by parental attention through the motivation of learning mathematics of grade IX Junior High School students in Turatea district of Jeneponto district during the covid-19 pandemic with a research sample of 125 students. Data collected using instruments: (1) parental attention questionnaires; (2) learning motivation questionnaire; and (3) tests of mathematical learning outcomes. Data analysis is done with descriptive analysis techniques to describe the characteristics of respondents' scores namely mean, satandar deviation, variance, minimum, and maximum, while to test hypotheses is done with inferential analysis using path analysis. The interpretation results show that: (1) students' mathematical learning outcomes in the conditions of the covid-19 pandemic are significantly influenced by parental attention; (2) students' mathematical learning outcomes in the conditions of the covid-19 pandemic are significantly influenced by student learning motivation; (3) student learning motivation in the condition of the covid-19 pandemic is significantly influenced by parental attention; and (4) student learning outcomes in the conditions of the covid-19 pandemic are significantly influenced by parental attention through student learning motivation.